Senyapan Pada Ujaran Iwan Fals di Acara Talkshow Kick Andy “Akhirnya Iwan Fals Bicara”: A Smile at Iwan Fals's Speech at the Kick Andy Talkshow "Finally Iwan Fals Talk" - Rahmawati, Dian Lufia (Anterior Jurnal, 2014)
Paused phenomenon needs to be studied through research that is useful to add information about the disciplines of speech production psycholinguistics. The focus of this research are: (1) what percentage of paused that occur during Iwan Fals deliver answers?; (2) What kind paused happened?; and (3) what is the reason or cause of pause? This study used a qualitative approach and descriptive analysis method. The research objectives are recording the show Kick Andy "Finally Iwan Fals Talk" sequel 3/25 uploaded at http:/ www.youtube.com by nengsalse on February 5, 2010, with the subject of the research is Iwan Fals and the object of research is speech Iwan Fals. Based on the results of the calculation of the length of time or duration paused contained in the speech Iwan Fals in the show Kick Andy "Finally Iwan Talk", paused occurred for 30 seconds, or 23.8% of the speaking time for 126 seconds. In the speech, Iwan Fals paused there are two types, namely paused silent and paused filled. Some of the reasons for the speech paused Iwan Fals, among others: (1) take a breather; (2) already started with the utterance, but in fact the whole sentence is not ready for it; (3) forgotten in certain words are needed; (4) hesitant because remembering past events; (5) The search for the right words to say; and (6) of prudence.